Occupational Exposure to Poorly Soluble Low Toxicity Particles and Cardiac Disease: A Look at Carbon Black and Titanium Dioxide - McCunney, Robert J.; Yong, Mei; Warheit, David B.; Morfeld, Peter (Frontiers in Public Health, 2022)
Environmental particulate exposure and the potential risk to people with cardiac disease has aroused scientific and regulatory interest worldwide. Epidemiological studies have shown associations between exposure to airborne environmental particles and mortality from cardiac disease. Few studies, however, have examined cardiovascular effects from occupational exposure to poorly soluble particles of low toxicity such as manufactured carbon black (CB) and titanium dioxide (TiO2).